Microbial biomass in a haplic gleysol in the Mato Grosso State Pantanal - Campos, Daniela Tiago da Silva; Martins, Maíra de Emílio; Messias, Indira Ashant Martins; MEdeiros, Patrícia Teles (Comunicata Scientiae, 2018)
The Pantanal is a biome that lives under water conditions and resists to two very distinct periods: flooded and drained. The objective of this study was to evaluate the behavior and quantify the microbial biomass during the flood period, in soils under riparian forest and cerrado vegetation in Mato Grosso State pantanal, at two depths. At depths of 0.00-0.05 m, the highest levels of C-BM and RB were found in cerrado soils; for the metabolic quotient no differences were observed in the two vegetations; the total organic carbon content was higher in riparian forest soils and the microbial quotient was higher in cerrado soils. Bacteria and fungi were found to be more abundant in the cerrado soil at the two evaluated depths and the actinomycetes in the forest. It is concluded that in the flood period there are the presence of active microorganisms which produce a differentiated biomass due to the phytophysiognomy of the location.